The Role of Mobile Service in Improving the Effectiveness of Property Tax Collection in Pakal Subdistrict, Surabaya - Afiyah Afiyah; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2026)
This study explains how mobile services improve the effectiveness of Property Tax (PBB) collection in Pakal Subdistrict, Surabaya. Mobile services are a public service innovation from the Regional Revenue Agency (Bapenda) of Surabaya. The mobile service aims to reach taxpayers who face transportation difficulties. It allows taxpayers to access service offices without having to travel long distances. This study employs a qualitative descriptive method. Field observations were conducted directly during an internship. The study also reviewed official documents and literature on regional taxation. Based on the research, the mobile service facilitates access for taxpayers in Pakal Subdistrict. The distance of Pakal Subdistrict from the city center poses a challenge in paying property tax. The mobile service reduces this challenge. The mobile service also improves taxpayer compliance. This occurs because field officers approach taxpayers directly. This study concludes that the mobile service is important as an effective alternative for tax payment. This service increases Surabaya City’s PBB revenue and improves the relationship between the local government and the community. Moving forward, additional human resources are needed. Expanding the operational schedule is also necessary so that this service provides maximum benefits.